2020
DOI: 10.1080/14737167.2021.1840357
|View full text |Cite
|
Sign up to set email alerts
|

Real-world reduction in healthcare resource utilization following treatment of opioid use disorder with reSET-O, a novel prescription digital therapeutic

Abstract: Introduction: Buprenorphine medication assisted treatment (B-MAT) adherence for opioid use disorder (OUD) is suboptimal. reSET-O, an FDA-cleared prescription digital therapeutic, delivers neurobehavioral therapy (community-reinforcement approach+fluency training+contingency management) to B-MATtreated OUD patients. Methods: This retrospective claims study (10/01/2018-10/31/2019) evaluated healthcare resource utilization up to 6 months before/after reSET-O initiation. Repeated-measures negative binomial models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 17 publications
5
36
0
Order By: Relevance
“…One evaluation of re-SET-O (i.e., during typical day-to-day clinical care) found that of the 3,144 patients followed across 30 states, 66% were abstinent as defined by self-report or drug negative urinalysis (missing data were considered positive; Maricich et al, 2020). Another study found decreases in healthcare utilization (e.g., emergency room and hospital visits) following use of re-SET-O with an estimated total savings of $750,000 for the 351 treatment patients (i.e., savings of $2,150 per patient) (Velez et al, 2021).…”
Section: Cigarette Smoking and Substance Use Disordersmentioning
confidence: 99%
“…One evaluation of re-SET-O (i.e., during typical day-to-day clinical care) found that of the 3,144 patients followed across 30 states, 66% were abstinent as defined by self-report or drug negative urinalysis (missing data were considered positive; Maricich et al, 2020). Another study found decreases in healthcare utilization (e.g., emergency room and hospital visits) following use of re-SET-O with an estimated total savings of $750,000 for the 351 treatment patients (i.e., savings of $2,150 per patient) (Velez et al, 2021).…”
Section: Cigarette Smoking and Substance Use Disordersmentioning
confidence: 99%
“…In November 2020, we published in this journal a retrospective claims study evaluating changes in healthcare resource utilization following the initiation of reSET-O among 351 predominantly Medicaid-covered (82.6%) patients with OUD [7]. That analysis showed a net reduction in medical costs of 2,150 USD per patient 6 months post initiation of reSET-O, driven in large part by a reduction in inpatient (IP) stays and emergency department (ED) visits, but also by a reduced utilization of presumptive and definitive drug testing for a variety of substances, and through the substitution of face-to-face counseling sessions (CPT codes for individual and group psychotherapy: 90,785-90,876).…”
Section: Evidence Of Long-term Real-world Reduction In Healthcare Resource Utilization Following Treatment Of Opioid Use Disorder With Rementioning
confidence: 99%
“…Over the period of time, the demand for healthcare facilities has increased exponentially all over the world (Pantzartzis et al, 2017;Velez et al, 2021). Healthcare services play an essential role in the socioeconomic development of any nation.…”
Section: Introductionmentioning
confidence: 99%